A note on the geographical aspect of marriages: marriage amongst the Malays in the Kelang District as an illustration. - Abdul Samad Hadi ,; Sham Sani, (Universiti Kebangsaan Malaysia, 1974)
Aspect of the spatial characteristic of Malay marriages in the Kelang district for 1961-1970 are described using the straight line distance measurement between spouses as the main focus of interest. Over the study period it is found that a majority of marriages took place between individuals who lived close by suggesting an intense social contacts within a limited area. Using the trend line, it is observed that the average mean distance tends to increase over the decade for the Malays in the Kelang district. If the mean distances could be taken to have reflected the mean area of social interaction for the community, over the decade the mean area of social interaction increased over the study period.